Influence of genetic suscetibility on the incidence and mortality of COVID-19 (SARS-COV-2) (Research, Society and Development, 2021)
This study aimed to carry out a literature review on the influence of genetic susceptibility on the incidence and mortality of COVID-19. It is a descriptive review of the literature carried out in the PUBMED and Science direct databases using the following descriptors: genetic susceptibility “AND “COVID-19”. The inclusion criteria were scientific articles available for free, in English, Spanish and Portuguese, which were published in 2020. Duplicate articles between databases were excluded. At the end, 58 studies followed the established criteria. The ACE2 and TMPRSS2 genes have the potential for prophylactic and therapeutic intervention in the early stages of SARS-CoV-2 infection, playing a crucial role in the entry of the virus into host cells. In addition, the locus of Human Leukocyte Antigen (HLA) appears to be crucial to influence the susceptibility and severity of COVID-19. Male individuals have a higher mortality and severity rate for COVID-19, being related to a more significant expression of ACE2 and differences in the epigenetic regulation of ACE2. Genetic susceptibility can contribute to the interindividual clinical variability associated with COVID-19, allowing for an evidence-based risk assessment leading to personalized preventive measures and therapeutic options.